Recirculating aquaculture - Timmons, Michael B. (Cayuga Aqua Ventures, 2007)
The text book is fully referenced and provides a very complete list of tables on conversion factors and other pertinent information specific for aquaculture. Several chapters are written by authors who are well known in the aquaculture community and combined have over 100 years of experience in aquacultural engineering. All are prominent members of the Aquacultural Engineering